How Art Works - Sarah Hull (India Usborne Publishing, Limited, 2020)
What is art? Where do artists get their ideas from? How do artists make pictures look "real"? This lively book answers these questions and many more, to explore how art works. It features scores of cartoons and over 65 full-colour reproductions, including works by Leonardo da Vinci, Pablo Picasso, Frida Kahlo, Bridget Riley and Damien Hirst. Covers key ideas and techniques, from Classical sculptures to Cubist paintings and contemporary art. Stylish and engaging illustrations by Ana Seixas will help inspire a new generation of art lovers. Invites children to look closely at art and start thinking about it for themselves.
Keywords: How We Express Ourselves -- -Art